Relative reproductive phenology and synchrony affect neonate survival in a nonprecocial ungulate. (28th September 2020) - Michel, Eric S.; Strickland, Bronson K.; Demarais, Stephen; Belant, Jerrold L.; Kautz, Todd M.; Duquette, Jared F.; Beyer, Dean E.; Chamberlain, Michael J.; Miller, Karl V.; Shuman, Rebecca M.; Kilgo, John C.; Diefenbach, Duane R.; et al.
Abstract: Degree of reproductive synchronization in prey is hypothesized as a predator defense strategy reducing prey risk via predator satiation or predator avoidance. Species with precocial young, especially those exposed to specialist predators, should be highly synchronous to satiate predators (predator satiation hypothesis), while prey with nonprecocial (i.e. altricial) young, especially those exposed to generalist predators, should become relatively asynchronous to avoid predator detection (predator avoidance hypothesis). The white‐tailed deer Odocoileus virginianus in North America is an example of a nonprecocial ungulate that uses the hider strategy early in life; its primary predator (coyote; Canis latrans ) is a generalist, making white‐tailed deer a good model species to test the predator avoidance hypothesis. We used birth dates and known fates of white‐tailed deer neonates ( n = 1, 032) across nine study sites varying in relative synchrony and predator assemblages to test the predator avoidance hypothesis. We predicted that relative birthing asynchrony of the population would increase relative survival at the population level; therefore, at the individual scale, neonate birth date nearer to mean birthing date in a respective population would not influence individual survival. Coyotes were responsible for the majority of predation events, and survival of those neonates increased the closer the individual was born to peak birthing season in each respective population. Also, at the population level, reproductive asynchronization negatively affected survival. Contrary to the predator avoidance hypothesis, our data indicate patterns in neonate survival for white‐tailed deer better support the predator satiation hypothesis at the individual and population level. Additionally, coyotes may present a selective force great enough to shift reproductive synchrony such that predator satiation may become a feasible defense strategy for neonates at local spatial scales. Our results indicate that synchronizing reproduction may still be the most effective strategy to reduce individual predation risk from generalist predators, particularly when the window of heightened resource availability to the prey is narrow. A free Plain Language Summary can be found within the Supporting Information of this article. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article.